1980
DOI: 10.1017/s0022172400026759
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B serology in Greek prostitutes: significance of the different serum markers

Abstract: One hundred and ninety-eight prostitutes (mean age 41-8 years) and 117 control women of low socio-economic class (mean age 43-8 years) were tested by solid-phase radioimmunoassay for hepatitis B surface antigen (HBsAg), its antibody (antiHBs) and antibody to hepatitis B core antigen (anti-HBc). The prevalence of HBsAg was higher among prostitutes (11% v. 4 %, P 0-06). This difference was accounted for by the higher infection rate of prostitutes to hepatitis B virus (HBV) (97% v. 45%, P < 106), since the propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Previous data of ours regarding all the screened Hellenic Armed Forces blood donations in a 7-year period (1976±1982) indicated a seropositivity rate of 4´13% (n 213 167). In 1979, the prevalence of HBsAg among randomly selected female controls was found consistently to be 4% (n 117; Kaklamani et al, 1980). Recently, in a prevalence study of a randomly selected sample of the general population in Crete, HbsAg seroprevalence ranged from 0 to 1´2% (n 257; Lionis et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data of ours regarding all the screened Hellenic Armed Forces blood donations in a 7-year period (1976±1982) indicated a seropositivity rate of 4´13% (n 213 167). In 1979, the prevalence of HBsAg among randomly selected female controls was found consistently to be 4% (n 117; Kaklamani et al, 1980). Recently, in a prevalence study of a randomly selected sample of the general population in Crete, HbsAg seroprevalence ranged from 0 to 1´2% (n 257; Lionis et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…An HBsAg seroprevalence rate of 3´3% was found over the same time period among registered female and transsexual sex workers (n 273; Tsakris et al, 1997), four times greater than the rate in our sporadic donor population. In the past (Kaklamani et al, 1980), the rate among female workers was found to be 11%.…”
Section: Discussionmentioning
confidence: 99%
“…An obvious trend of reduction of the HBV prevalence is observed in other traditionally high-risk groups, such as prostitutes, since the percentage of HBsAg-seropositivity (11%) at the early 80s has been reduced to 3.3% in the late 90s; these data need to be reevaluated because of the high percentage of people trafficking for sexual reasons, mainly from countries of median-high HBV prevalence to our country, who are not reported or sanitary controlled and are thought to represent the most significant cause of HBV transmission in our days [ 29 , 30 ]. Data from a study of the Department of Public Order were presented in daily press and according to conservative calculations there are more than 14 000 people who are illegally sexually prostituted in our country.…”
mentioning
confidence: 99%